Evolving portrayals: Unveiling the shifting trends in advertising - Poongulaly, S.; Anutharsi, G. (Trincomalee Campus, Eastern University Sri Lanka, 2024)
Mass media is the primary means of communication for reaching the masses. Different studies have made it clear that objectification through mass media has had a tremendous impact on the world. Advertising is “the non-personal communication of information usually paid for being persuasive about products, services or ideas by identified sponsors through the various media”. Advertising has long been a mirror reflecting societal norms and expectations, including those regarding gender roles. However, as society progresses and perspectives evolve, so does the portrayal of men and women in advertising. This study examines the evolution of gender portrayals in Indian Tamil advertisements, analyzing how they reflect and shape societal attitudes, by employing a content analysis framework, the research aims to understand the extent to which contemporary advertisements challenge or reinforce traditional gender stereotypes, while also exploring emerging representations of gender diversity and inclusivity. In this way, the study aims to find out the changing trends of gender portrayal in Indian Tamil advertisements through some representative ads based on these research questions. RQ1: How have portrayals of gender roles in Indian Tamil advertisements evolved over time? RQ2: To what extent do contemporary Indian Tamil advertisements challenge or reinforce traditional gender stereotypes? RQ3: How do contemporary Indian Tamil advertisements represent diverse gender identities and sexual orientations? The researcher observed the ten product advertisements, old and new versa. Content analysis has been conducted to find out the transformation. As the conclusion of this study, the role of gender in advertising is undergoing a profound transformation, driven by evolving societal attitudes and consumer expectations. Advertisers can shape narratives that reflect and inspire positive social change by challenging stereotypes, championing diversity, and promoting inclusivity. Further, Brands are investing in storytelling, user-generated content, and influencer collaborations to forge authentic connections with their audience.
Keywords: Breaking stereotypes; Gender; Indian advertisements; Portrayal